If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying l + (-15) = 29 l + -15 = 29 Reorder the terms: -15 + l = 29 Solving -15 + l = 29 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + l = 29 + 15 Combine like terms: -15 + 15 = 0 0 + l = 29 + 15 l = 29 + 15 Combine like terms: 29 + 15 = 44 l = 44 Simplifying l = 44
| p=300/0.06*4 | | 5.6x=-39.2 | | -4.9t^2+2t+450=0 | | f-(11)=8 | | 2x^2+3x+22=0 | | √20/4.9 | | 3sin^4x=1 | | y=21/2-5 | | 3/5×5/9= | | 2z=144 | | 8x+15=185 | | -29=-5d+70 | | 3x^2+26x-34=0 | | 14x-22=314 | | 9x^6+36x^4-4x^2-16=0 | | 6x^2=24x-18 | | 5(2f-2)=4(3f-5) | | 3m^2+6mn+3n^2-48= | | 9(7+6f)=-27 | | 43.25=1.25t+7 | | 18/9x-28=10 | | w^2-7w+20=0 | | -30=0.9x+16.8 | | xy=52 | | x+4-14=30 | | 44-7x=x^2 | | -4/5(x8)=12 | | 11w+-11=0 | | 25=5(4s-3) | | 2/3×13 | | 8y+5y=5y-5+2y | | -8r-6r=-19 |